Steps in Introducing Reading Books to Children - Girsang, Martina; Meidar Lafau, Roh; Wati Sihombing, Riska; Mutiara Br Sinaga, Ruth; Angelina Br Hutahayan, Hertina (International Journal of Education and Digital Learning (IJEDL), 2023)
The purpose of the article is to educate the children by reading books. It shows the step by step in introducing reading books to children. An introducing reading books to children on the early age is important. Books are a storehouse of knowledge that needs to be presenting to the children until they grow up . The role of parents towards children is very important because the way parents educate children will determine their abilities and creativity for their future. Parents should be responsible for the growth and development of children in building children's character by introducing small things around children such as books. The function is to ensure that the small family in their own children are provide facilities and infrastructure to develop skills as provisions in social life, as well as media in instilling social and cultural values as early as possible. The method used in this study is the descriptive method and qualitative approach.